Unusual low temperature relaxation behavior of crosslinked acrylonitrile-butadiene co-polymer. (6th January 2021) - Basu, Debdipta; Banerjee, Shib Shankar; Chandra Debnath, Subhas; Malanin, Mikhail; Amirova, Lyaysan; Dubois, Philippe; Heinrich, Gert; Das, Amit
Abstract: Conventional crosslinking of rubbers (using sulphur and peroxide vulcanization) usually leads to covalent rubber network junctions. The present article reports about a new unconventional crosslinking of acrylonitrile butadiene copolymer (NBR) by zinc chloride (ZnCl2 ). This crosslinked NBR displayed very interesting relaxation properties below the glass transition temperature. In this work, detailed chemical mechanistic pathways were suggested and correlated with the low-temperature relaxation dynamics of the crosslinked material. Fourier-transform infrared spectroscopy analysis clearly indicated a coordination effect between zinc and nitrile groups. At lower temperatures, beside the glass transition, another relaxation process (β relaxation) was detected. Interestingly, a hydrolyzed crosslinked sample showed even two other additional relaxation processes. The origin of such relaxations was critically discussed from the viewpoints of modification of the polymer chains as well as low molecular weight fragments of the polymer. Graphical abstract: Image 1 Highlights: Multiple Low temperature relaxation behavior of Acrylonitrile butadiene rubber (NBR). Metal ion mediated crosslinking of nitrile rubber. Heterogeneity in crosslinking in NBR with non-classical curing agent. Zinc-nitrile complex formation and subsequently this complex could generate a cross-metathesis type reaction resulting to low molecular weight polymers.